Teoria da argumentação na língua : nova perspectiva para o ensino da leitura desde a educação básica - Rahal, Cláudia Belmonte (2015)
Official organs have divulged negative indices regarding the results of reading skills tests, which points out the need for innovative initiatives from the school on this issue. In view of that, this work aims to present the Theory of Argumentation in Language (ANL), by Oswald Ducrot with collaboration of Jean-Claude Ascombre and, currently, of Marion Carel, as a possibility of change of the conception in regard to the reading teaching in Basic Education. We start from the ANL perception according to which reasoning is building sense, and sense is possible through the relation set among the words, inherent to language and aprehended on the discourse. The goal is to consider this perspective during the act of reading and understanding texts. Therefore, we have chosen this theoretical approach because ANL allows us to analyze language in use, which comes to agree with what we understand as essential on working with text reading. We believe in a work which understands that argumentation in language explains argumentation on discourse and that this linguistic argumentation is established by the relation among the words. That has led us to choose didactic transposition from the basic concept of relation of ANL to teaching. In order to emphasize the need for change on teaching perspective, we have analyzed reading activities on 6th grade didactic books, the level in which the curriculum organization changes from single-teacher-to-all-subjects system to assume a multiple-treacher character. Aiming to prove the possibility of change under ANL ideas, we have prepared purposes of reading activities based on the principle of relation. These activties will be presented in a guide format to drive the work of the teachers and, as a consequence, the learning of the students. We believe that the use of the theory of Oswald Ducrot will enable schools to promote a more meaningful teaching, in which the study of reading will be focused on a reader attentive to the linguistic expressions as argumentative buildings on the use of language. Thus, masters and pupils will be challenged to reflect upon the argumentaive guidance present all over the text.